PENINGKATAN HASIL BELAJAR MEMBACA PEMAHAMAN MELALUI PENERAPAN APLIKASI QUIZIZZ SISWA SMP - Lukman; Mila Karmila (Jurnal Riset Guru Indonesia, 2024)
Improving Reading Comprehension Learning Outcomes by Implementing the Quizizz Application for Class VII Students of SMP Negeri 3 Bantaeng The aim of this research is that Quizizz can improve reading comprehension learning outcomes by implementing the Quizizz application for class VII students at SMP Negeri 3 Bantaeng. The research design used is a classroom action research design. The implementation procedure in this research goes through stages which include: Preliminary study, planning, action implementation, observation and reflection. This research data is in the form of data on the process and results of learning to read comprehension for class VII SMP Negeri 3 Bantaeng. This research aims to improve the reading comprehension skills of Class VII students at SMP Negeri 3 Bantaeng through the use of actions obtained from observations, interviews, field notes, documentation. The results of the research showed that there was an increase in student learning activities from cycle I to cycle II, namely an increase in the number of students listening to the teacher's explanation, asking questions, answering questions, collaborating in groups and submitting responses. Student learning outcomes also increased, namely the average score obtained in cycle I was 67% and in cycle II was 91.37%. So that the application of the Quizizz application can increase the frequency of liveliness and activity in the teaching and learning process in accordance with student observations during the implementation of classroom action research in just two cycles.